Does U.S. Marine Corps Recruit Training Constitute a Type of Civic Education?. Issue 1 (2nd January 2017) - Hodges, Eric B.
ABSTRACT: In what respects can military basic training affect veterans' civic identities? According to a 2015 report published by the National Conference on Citizenship (NCoC), military service positively affects civic health. While social scientists have also noted this possible connection, little attention has been paid to how and why this link might exist. To test the purported relationship between military training and increased civic capacities, I explored the United States Marine Corps' (USMC) Recruit Training program. I conducted 20 semi-structured, in-depth interviews with 17 enlisted Marine veterans and Marine drill instructors (DI) to ascertain their perceptions of the pedagogical aspirations of their service's recruit training. The study's participants reported that Marine Corps Recruit Training does seek to inculcate skills, values, and habits that are consistent with a civic identity as discussed in the civic-engagement and civic-education literature.